Operation World [the definitive prayer guide to every nation] - Mandryk, Jason (Downers Grove, Ill. IVP Books [u.a.], 2011)
The world and its regions -- The world -- Africa -- The Americas -- Asia -- Europe -- Pacific -- Countries -- Afghanistan -- Albania -- Algeria -- American Samoa -- Andorra -- Angola -- Anguilla -- Antigua & Barbuda -- Argentina -- Armenia -- Aruba -- Australia -- Austria -- Azerbaijan -- Bahamas, The -- Bahrain -- Bangladesh -- Barbados -- Belarus -- Belgium -- Belize -- Benin -- Bermuda -- Bhutan -- Bolivia -- Bosnia -- Botswana -- Bougainville see Papua New Guinea -- Brazil -- Britain see United Kingdom -- British Indian Ocean Territory -- British Virgin Islands -- Brunei -- Bulgaria -- Burkina Faso -- Burma see Myanmar -- Burundi -- Byelorussia see Belarus -- Cambodia -- Cameroon -- Canada -- Canary Islands see Spain -- Cape Verde Islands -- Caribbean see The Americas -- Caroline Islands see Micronesia -- Cayman Islands -- Central African Republic -- Chad -- Channel Islands see United Kingdom -- Chile -- China, People's Republic of -- China, Hong Kong -- China, Macau -- China, Taiwan -- Christmas Island see Australia -- Cocos (Keeling) Islands see Australia -- Colombia -- Comoros -- Congo, Democratic Republic of the (Also Congo-DRC or DRC) (Kinshasa) -- Congo, Republic of (Brazzaville) -- Cook Islands -- Costa Rica -- Cote d'Ivoire -- Croatia -- Cuba -- Cyprus -- Czech Republic -- Denmark -- Djibouti -- Dominica -- Dominican Republic -- East Timor see Timor Leste -- Eastern Samoa see American Samoa -- Ecuador -- Egypt -- Eire see Ireland -- El Salvador -- England see United Kingdom -- Equatorial Guinea -- Eritrea -- Estonia -- Ethiopia -- Eurasia see Europe and Asia -- Faeroe Islands -- Falkland Islands -- Federated States of Micronesia (FSM) see Micronesia -- Fiji -- Finland -- France -- French Guiana -- French Polynesia -- Gabon -- Gambia -- The Gaza Strip see Palestine -- Georgia -- Germany -- Ghana -- Gibraltar -- Gilbert Islands see Kiribati -- Great Britain see United Kingdom -- Greece -- Greenland -- Grenada -- Guadeloupe -- Guam -- Guatemala -- Guinea --
Includes bibliographical references
Keywords: Missions -- Handbooks, manuals, etc; Christian Sects -- Handbooks, manuals, etc; Geography -- Handbooks, manuals, etc; Christian Sects; Devotional calendars; Geography; Missions; Religions -- Handbooks, manuals, etc